The prevalence of chronic pelvic pain in women in the United Kingdom: a systematic review. - Zondervan, K; Yudkin, P; Vessey, M; Dawes, MG; Barlow, D; Kennedy, S (1998)
OBJECTIVE: To obtain a prevalence estimate for chronic pelvic pain in women in the United Kingdom by analysing published data. DESIGN: Systematic review of published papers. SETTING: The general population or hospitals in the United Kingdom. POPULATION: Women participating in relevant community surveys or control women participating in hospital-based studies. METHODS: Papers were retrieved by systematically searching the databases MEDLINE, EMBASE and PsycLit, and by hand searching. Studies were included if they 1. were community-based and reported prevalence rates of chronic pelvic pain, dyspareunia, dysmenorrhoea, or abdominal pain, or 2. referred to a clinical population but reported prevalence rates in a disease-free control group. MAIN OUTCOME MEASURES: Prevalence rates for chronic pelvic pain including any overlap with dyspareunia, dysmenorrhoea and abdominal pain. RESULTS: No community-based study has been performed that provides an estimate of the prevalence of chronic pelvic pain in the general UK population. A rate of 39% was reported in women undergoing laparoscopy for sterilisation or investigation of infertility in the single study from the United Kingdom investigating chronic pelvic pain unrelated to menstruation or intercourse. Prevalence rates for dyspareunia, dysmenorrhoea, and abdominal pain found in UK community-based studies were 8%, 45% to 97%, and 23% to 29%, respectively, but definitions used varied greatly. CONCLUSIONS: Because chronic pelvic pain can reduce the quality of life and general wellbeing, there is a need for a community-based study into the prevalence of chronic pelvic pain and its effect upon the lives of women in the UK.